Seminar dan Workshop "AI in Action: Etika dan Implementasi Kecerdasan Artifisial" bagi Karang Taruna RT 06 RW 11 Kelurahan Penggilingan, Kecamatan Cakung, Jakarta Timur - Zaky Pratama; Chantika Dian Anugrah; Athif Nur Abdillah; Muhammad Azizsyah Putra; Achmad Suhendar; Mohamad Fajar Mutaqin; Rully Mujiastuti; Nurvelly Rosanti; Popy Meilina; Yana Adharani; Sitti Nurbaya Ambo (KENDURI : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
The rapid development of Artificial Intelligence (AI) offers new opportunities to boost the productivity of community organizations. However, limited AI literacy and lack of understanding regarding ethical AI use remain significant challenges. This community service program was designed to improve members’ understanding of AI concepts, ethical practices, and practical skills in using Google Gemini, Canva AI, and Suno AI for supporting organizational activities. Held on July 5, 2026, at the Karang Taruna Secretariat (RT 006 RW 011, Penggilingan Village, Cakung District, East Jakarta), the program featured seminars, workshops, demonstrations, hands-on practice, and mentoring. Evaluation methods included pre-tests, post-tests, and feedback questionnaires delivered via Google Forms. All participants achieved perfect scores on both the pre-test and post-test, making it impossible to measure learning gains using the Normalized Gain method due to the ceiling effect. Despite this, participants gave highly positive feedback on the quality of learning materials, presentation methods, and overall program implementation. They also successfully created AI-assisted outputs such as event concepts, promotional posters, and background music using Google Gemini, Canva AI, and Suno AI. These results demonstrate that combining seminars, demonstrations, hands-on practice, and mentoring can strengthen AI literacy, enhance practical skills, and encourage ethical, responsible AI use. Additionally, this program offers a practical model for advancing digital literacy and supporting sustainable digital transformation in youth organizations and community groups.